Plectranthias purpuralepis sp. nov., a new anthiadine perchlet from northern Taiwan (Perciformes: Serranidae) - Tang, Chi-Ngai; Lai, Nok-Wai; Ho, Hsuan-Ching (Zootaxa, 2020)
A new species of Plectranthias Bleeker is described on the basis of 16 specimens collected from northern Taiwan. The new species, Plectranthias purpuralepis sp. nov. can be distinguished from its congeners in having pectoral and pelvic fins mostly covered with small scales, some white scales on dorsum turn purple when preserved, and the following combination of characters: dorsal-fin elements X, 16–17; 3rd dorsal-fin spine longest; pectoral-fin rays 14, all branched except for uppermost simple ray; principal caudal-fin rays 9+8; pored lateral-line scales 33–36; 6 diagonal rows of large scales on cheek; circumpeduncular scales 14; ca. 7 rows of large predorsal scales, 2 irregular rows of small scales extending to a line through posterior nostrils; no scales on maxilla and chin; posterior margin of preopercle serrated, ventral margin with 2 antrorse spines; and the greatest body depth 2.9–3.0 in SL.